Modeling CH4 and N2O emission patterns and mitigation potential from paddy fields in Shanghai, China with the DNDC model. (February 2020) - Zhao, Zheng; Cao, Linkui; Deng, Jia; Sha, Zhimin; Chu, Changbin; Zhou, Deping; Wu, Shuhang; Lv, Weiguang
Abstract: The flooded paddy field ecosystem is an important source of CH4 and N2 O emissions from agricultural lands. Denitrification-Decomposition (DNDC), a process-based model, was used in this study to evaluate the effects of different field management practices on CH4 and N2 O emissions from flooded paddy fields in Shanghai, China. The results indicated that the predicted seasonal patterns of CH4 (R 2  = 0.76, ME = 0.71) and N2 O (R 2  = 0.71, ME = 0.67) emissions were in line with the observations from our experimental paddy field under traditional management practices. The total CH4 and N2 O fluxes from paddy fields in the Shanghai region in the 2013 rice season reached 32, 300 and 175 tons, respectively, and varied widely across 101 simulated rice-cultivating towns. A sensitivity analysis indicated that CH4 emissions were positively correlated with the organic fertilizer rate, the straw returned fraction, the tillage depth and the soil organic carbon (SOC) content and negatively correlated with the soil clay fraction. N2 O emissions had a positive relationship with precipitation, the urea rate, the tillage depth and the SOC content and a negative relationship with the soil pH and the clay fraction. Based on the sensitivity analysis, four field management variables, including the fertilization rate, the irrigation method, the straw returned fraction and the tillage depth, were selected to construct several management scenarios for the DNDC scenario simulation tests. The simulated results indicated that reducing the rate of fertilization by 20% combined with moistening irrigation (keeping the paddy soil saturated with water but not covered with a layer of water) was the best practice for long-term sustainable management of paddy fields. This best management practice could reduce integrated emissions of CH4 and N2 O (CO2 -equivalent) by 33%, while maintaining optimal rice yields. However, straw returning and deep plowing increased CH4 emissions from paddy fields in Shanghai. Graphical abstract: Unlabelled Image Highlights: CH4 and N2 O emissions from paddy fields in Shanghai region were simulated with the DNDC model. CH4 and N2 O emissions could be substantially reduced with management optimization. Reducing fertilization combined with moistening irrigation was the best management practice. The applicability of the DNDC model in flooded paddy field was validated.